Affected differentiation and function of innate lymphoid cells type 2 in the absence of the Th2-and Th1-associated transcription factor NIP45 - Koch, Sonja; Springel, R.; Knipfer, Lisa; Wirtz, Stefan; Finotto, Susetta (2018)
EVALuna2:207770

Emergence of novel ST1299 vanA lineages as possible cause for the striking rise of vancomycin resistance among invasive strains of Enterococcus faecium at a German university hospital - Valenza, Giuseppe; Eisenberger, David; Voigtländer, Sven; Alsalameh, Rayya; Gerlach, Roman; Koch, Sonja; Kunz, Bernd; Held, Jürgen; Bogdan, Christian (Microbiology Spectrum, 2023)
IMPORTANCE: The proportion of VREfm among all Enterococcus faecium isolated from blood cultures in German hospitals has increased in the period 2015-2020 from 11.9% to 22.3% with a country-wide spread of the clonal lineage ST117/CT71 vanB. In this study, we provided useful information about the genetic diversity of invasive strains of E. faecium. Moreover, our findings confirm the nosocomial spread of novel ST1299 vanA lineages, which recently had a rapid expansion in Austria and the south-eastern part of Germany.
CRIS-Team Scopus Importer:2023-12-29
Keywords: bloodstream Infection; core genome multilocus sequence typing; Enterococcus faecium; ST1299 vanA; vancomycin resistance

FAM13A is associated with non-small cell lung cancer (NSCLC) progression and controls tumor cell proliferation and survival - Eisenhut, Felix; Heim, Lisanne; Trump, Sonja; Mittler, Susanne; Sopel, Nina; Andreev, Katerina; Ferrazzi, Fulvia; Ekici, Arif Bülent; Rieker, Ralf; Springel, Rebekka; Assmann, Vera Elisabeth; Lechmann, Matthias; et al. (OncoImmunology, 2017)
Genome-wide association studies (GWAS) associated Family with sequence similarity 13, member A (FAM13A) with non-small cell lung cancer (NSCLC) occurrence. Here, we found increased numbers of FAM13A protein expressing cells in the tumoral region of lung tissues from a cohort of patients with NSCLC. Moreover, FAM13A inversely correlated with CTLA4 but directly correlated with HIF1? levels in the control region of these patients. Consistently, FAM13A RhoGAP was found to be associated with T cell effector molecules like HIF1? and Tbet and was downregulated in immunosuppressive CD4(+)CD25(+)Foxp3(+)CTLA4(+) T cells. TGF?, a tumor suppressor factor, as well as siRNA to FAM13A, suppressed both isoforms of FAM13A and inhibited tumor cell proliferation. RNA-Seq analysis confirmed this finding. Moreover, siRNA to FAM13A induced TGF? levels. Finally, in experimental tumor cell migration, FAM13A was induced and TGF? accelerated this process by inducing cell migration, HIF1?, and the FAM13A RhoGAP isoform. Furthermore, siRNA to FAM13A inhibited tumor cell proliferation and induced cell migration without affecting HIF1?. In conclusion, FAM13A is involved in tumor cell proliferation and downstream of TGF? and HIF1?, FAM13A RhoGAP is associated with Th1 gene expression and lung tumor cell migration. These findings identify FAM13A as key regulator of NSCLC growth and progression.
EVALuna2:6835

IL-6 activated integrated BATF/IRF4 functions in lymphocytes are T-bet-independent and reversed by subcutaneous immunotherapy - Mousset, Stephanie; Koch, Sonja; Mousset, Stephanie; Graser, Anna; Reppert, Sarah; Uebel, Caroline; Reinhardt, Cornelia; Zimmermann, Theodor; Rieker, Ralf; Lehr, Hans A.; Finotto, Susetta (Scientific Reports, 2013)
IL-6 plays a central role in supporting pathological TH2 and TH17 cell development and inhibiting the protective T regulatory cells in allergic asthma. TH17 cells have been demonstrated to regulate allergic asthma in general and T-bet-deficiency-induced asthma in particular. Here we found an inverse correlation between T-bet and Il-6 mRNA expression in asthmatic children. Moreover, experimental subcutaneous immunotherapy (SIT) in T-bet((-/-)) mice inhibited IL-6, IL-21R and lung TH17 cells in a setting of asthma. Finally, local delivery of an anti-IL-6R antibody in T-bet((-/-)) mice resulted in the resolution of this allergic trait. Noteworthy, BATF, crucial for the immunoglobulin-class-switch and TH2,TH17 development, was found down-regulated in the lungs of T-bet((-/-)) mice after SIT and after treatment with anti-IL-6R antibody, indicating a critical role of IL-6 in controlling BATF/IRF4 integrated functions in TH2, TH17 cells and B cells also in a T-bet independent fashion in allergic asthma.

Immunoregulatory role of acid sphingomyelinase in allergic asthma - Sopel, Nina; Kölle, Julia; Dumendiak, Sonja; Koch, Sonja; Reichel, Martin; Rhein, Cosima; Kornhuber, Johannes; Finotto, Susetta (Immunology, 2019)
Acid sphingomyelinase (ASM) is one of the enzymes that catalyzes the breakdown of sphingomyelin to ceramide and phosphorylcholine. In this study, we aimed at elucidating the role of ASM in allergic asthma. We used an ovalbumin-induced murine model of asthma where we compared wild-type and ASM-deficient mice. In wild-type mice, secretory ASM activity in the bronchoalveolar lavage fluid was increased in the acute ovalbumin model, but not in a tolerogenic model. Furthermore, in the absence of ASM, the serum IgE level was reduced, compared with wild-type mice, while an accumulation of interstitial macrophages and foreign antigen-induced regulatory T cells along with exhausted CD4(+) PD1(+) T cells was observed in the lungs of ASM(-/-) mice. In conclusion, in the absence of ASM, we observed an accumulation of immunosuppressive antigen-induced regulatory T cells expressing Foxp3 and CTLA4 in the lung as well as multinucleated interstitial macrophages and exhausted CD4(+) PD1(+) T cells associated with inhibition of serum IgE in asthma.
CRIS-Team WoS Importer:2019-04-09

Immunoregulatory role of NFAT-interacting protein (NIP) 45 in adaptive and innate immune responses in allergic asthma - Koch, Sonja; Maeding, N.; Karwot, R.; Mirzakhani, H.; Springel, R.; Mittler, S.; Zimmermann, Theodor; Melichar, V. O.; Knipfer, Lisa; Wirtz, Stefan; Weiss, S. T. (2017)
EVALuna2:33897

Increased expression of nuclear factor of activated T cells 1 drives IL-9-mediated allergic asthma - Koch, Sonja; Graser, Anna; Mirzakhani, Hooman; Zimmermann, Theodor; Melichar, Volker O.; Woelfel, Marco; Croteau-Chonka, Damien C.; Raby, Benjamin A.; Weiss, Scott T.; Finotto, Susetta (Journal of Allergy and Clinical Immunology, 2016)
EVALuna2:25981

Targeted deletion of NFAT-Interacting-Protein-(NIP) 45 resolves experimental asthma by inhibiting Innate Lymphoid Cells group 2 (ILC2) - Koch, Sonja; Knipfer, Lisa; Kölle, Julia; Mirzakhani, Hooman; Graser, Anna; Zimmermann, Theodor; Kiefer, Alexander; Melichar, Volker O.; Rascher, Wolfgang; Papadopoulos, Nikolaos G.; Rieker, Ralf; Raby, Benjamin A.; et al. (Scientific Reports, 2019)
Here we investigated the role of NFAT-interacting protein (NIP)-45, an Interleukin (IL)-4 inducing Transcription Factor, and its impact on the differentiation of Group 2 Innate -Lymphoid -Cells (ILC2s) in the pathogenesis of asthma. NIP45, a transcription factor regulating NFATc1 activity, mRNA was found to be induced in the Peripheral Blood mononuclear cells (PMBCs) of asthmatic pre-school children with allergies and in the peripheral blood CD4+ T cells from adult asthmatic patients. In PBMCs of asthmatic and control children, NIP45 mRNA directly correlated with NFATc1 but not with T-bet. Targeted deletion of NIP45 in mice resulted in a protective phenotype in experimental asthma with reduced airway mucus production, airway hyperresponsiveness and eosinophils. This phenotype was reversed by intranasal delivery of recombinant r-IL-33. Consistently, ILC2s and not GATA3+ CD4+ T-cells were decreased in the lungs of asthmatic NIP45−/− mice. Reduced cell number spleen ILC2s could be differentiated from NIP45−/− as compared to wild-type mice after in vivo injection of a microcircle-DNA vector expressing IL-25 and decreased cytokines and ILC2 markers in ILC2 differentiated from the bone marrow of NIP45−/− mice. NIP45 thus emerges as a new therapeutic target for the resolution of the airway pathology, down-regulation of ILC2s and mucus production in asthma.
CRIS-Team Scopus Importer:2019-11-08

Th9 and other IL-9-producing cells in allergic asthma - Koch, Sonja; Sopel, Nina; Finotto, Susetta (Seminars in Immunopathology, 2017)
Allergic asthma is a worldwide increasing chronic disease of the airways which affects more than 300 million people. It is associated with increased IgE, mast cell activation, airway hyperresponsiveness (AHR), mucus overproduction and remodeling of the airways. Previously, this pathological trait has been associated with T helper type 2 (Th2) cells. Recently, different CD4(+) T cell subsets (Th17, Th9) as well as cells of innate immunity, like mast cells and innate lymphoid cells type 2 (ILC2s), which are all capable of producing the rediscovered cytokine IL-9, are known to contribute to this disease. Regarding Th9 cells, it is known that naïve T cells develop into IL-9-producing cells in the presence of interleukin-4 (IL-4) and transforming growth factor beta (TGF?). Downstream of IL-4, several transcription factors like signal transducer and activator of transcription 6 (STAT6), interferon regulatory factor 4 (IRF4), GATA binding protein 3 (GATA3), basic leucine zipper transcription factor, ATF-like (BATF) and nuclear factor of activated T cells (NFAT) are activated. Additionally, the transcription factor PU.1, which is downstream of TGF? signaling, also seems to be crucial in the development of Th9 cells. IL-9 is a pleiotropic cytokine that influences various distinct functions of different target cells such as T cells, B cells, mast cells and airway epithelial cells by activating STAT1, STAT3 and STAT5. Because of its pleiotropic functions, IL-9 has been demonstrated to be involved in several diseases, such as cancer, autoimmunity and other pathogen-mediated immune-regulated diseases. In this review, we focus on the role of Th9 and IL-9-producing cells in allergic asthma.
EVALuna2:25987